Lethal effect of heterologous Haemonchus contortus α- and β-tubulin expression in Leishmania tarentolae - Marc Borchert; Jürgen Krücken; Marion Müller; Georg von Samson-Himmelstjerna (PLoS ONE, 2026)
Benzimidazoles are widely used anthelmintics that target β-tubulin and disrupt microtubule formation, yet the precise mode of action and resistance mechanisms in parasitic nematodes remains incompletely understood. To investigate the processes, heterologous expression of Haemonchus contortus isotype-1 α-tubulin and isotype-1 β-tubulin linked to the selection markers nourseothricin and hygromycin, respectively, was attempted following integration into Leishmania tarentolae ssu(18S) loci. Transcription of both tubulin genes was confirmed by RT-PCR two days post-transfection. However, transgenic L. tarentolae failed to recover or enter exponential growth under antibiotic selection. In contrast, control constructs containing scrambled open reading frame integrated successfully and yielded viable and proliferating lines expressing the corresponding mRNAs. These findings indicate that translation of functional H. contortus tubulins is toxic to L. tarentolae , likely due to incompatibility with native tubulins and disruption of the native microtubule network, resulting in loss of motility and cell death. The study provides experimental evidence that cross-species tubulin expression can be lethal due to cytoskeletal interference, underscoring the functional specificity of tubulin subunits. This incompatibility represents a barrier to heterologous tubulin expression and suggests that controlled or inducible eukaryotic expression systems may be necessary for the functional production of nematode tubulins.